Trends and Correlations of Financial Ratios in PT Sepatu Bata Tbk - Hadi Sucipto, Rakhmat; Indrarti, Wahyu; Rosmita, Rosmita; Ivan Taruna, Helmy (Universitas Islam Nahdlatul Ulama Jepara, 2025)
This study aims to analyze the company's financial performance by looking at it from the perspective of liquidity, solvency, and profitability. To achieve this goal, this study utilizes secondary company data with quantitative and comparative descriptive research approaches. The research analysis focuses on current ratio, quick ratio, debt-to-asset ratio, debt-to-equity ratio, return on assets, and return on equity. The researchers compared trend analysis by comparing available data based on time changes. The results of the study show that in terms of liquidity, the company's financial condition is less convincing because current assets are under one time, while the quick ratio is even lower. The company also faces solvency problems, which is indicated by a debt ratio that is too high, especially in terms of the debt-to-equity ratio which has reached 346%. The company's profitability is not convincing because ROA and ROE have been recorded negative for the last four years from 2020 to 2023. The liquidity ratio has a negative relationship with the debt ratio but creates a positive correlation with the profitability ratio. The debt ratio always has an indirect relationship with other ratios